Development of An Open Journal Systems (OJS) Based Journal Article Publication E-Module for Students of Universitas Bosowa - Rahmat S. Bintang; Tarmizi Thalib (Jurnal Ilmiah Global Education, 2026)
Student barriers in publishing scientific articles such as limited guidance, insufficient academic writing skills, and a lack of technical understanding of the Open Journal Systems (OJS) highlight the need for digital learning innovation. This study aims to analyze the effectiveness of an OJS-based journal article publication e-module for students at Universitas Bosowa. The e-module was developed using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which enables systematic material development and the integration of theoretical concepts of scientific publication with practical steps for using OJS. The study employed a quasi-experimental approach with a one-group pretest–posttest design. The sample consisted of 30 students selected using a cluster sampling technique. The test instrument was developed based on two main components of the e-module: theoretical framework and practical activities. Data were analyzed using a paired sample t-test. The results indicate a significant improvement in students’ article publication abilities after using the e-module, with the mean pretest score of 10.80 increasing to 12.50 in the posttest (p = 0.006). These findings demonstrate that the e-module is effective in enhancing both the theoretical understanding and practical skills of students related to article publication through OJS. This study concludes that the development of the e-module serves as a strategic solution to strengthen students’ scientific publication literacy while supporting improvements in learning quality and higher education accreditation outcomes.